Konsep Pendidikan Iman dan Taqwa Perspektif Kitab Hidayatus Salikin Maslakil Muttaqqin - Vialinda Siswati; Siti Rahmah (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2022)
The importance of knowing and exploring the nature of a servant, knowing and exploring the nature and devotion of a servant to his Lord. This study discusses the sincerity of a person in every act or deed of service. And provide knowledge about the importance of knowing the science of success and piety. This type of research is a literature study that thoroughly explores the contents of the book by KH. Abd Shamad Al Falimbani entitled Hidayatus Salikin Fi Suluki Maslakil Muttaqqin who knows about how and piety and the ease of a person to understand the importance of knowing the meaning of way and piety. And the focus of the research: 1) What is the concept of faith education in the book Hidayatus Salaikin Fisuluki Maslakil Mutaqqin? 2) what is the concept of taqwa in the book Hidayatus Salikin Fi suluki maslakil mutaqqin? 3) how is the relevance of faith and piety in the perspective of the book Hidayatus Salikin fi suluki maslakil mutaqqin?. From the results of this study we can conclude that the importance of knowledge and piety. Those who have been ordered to believe and fear Allah SWT anytime and anywhere regardless of time and place. because of how and the piety of every human being sometimes has ups and downs, so knowing how to know and determine how to become a servant is included in the category of believing and pious servants. Because a servant who has faith and piety is guaranteed to be happy in this world and in the hereafter.